Detection and molecular characterization of Potato virus S (PVS, Carlavirus) from Colombia - Gil, José Fernando (2013)
In Colombia, potato crops are affected by a wide variety of viruses such as PVY, PLRV, PVX, PMTV and PVS. Unfortunately, there are very few studies on the biology, distribution and pathogenicity of these viruses; this situation is even worse for the latent virus PVS. In this work, we evaluated the presence of PVS in four Colombian provinces (Antioquia, Boyacá, Cundinamarca, Nariño) by the use of ELISA. We also studied the degree of molecular variation by sequence comparison of a segment of the gene encoding for the viral coat protein. In average, PVS was detected in 40% of 320 analyzed samples of potato leaves; the highest levels were observed in the East of Antioquia (49%) and Pasto (Nariño) (47%), while in the other regions ranged between 35% and 42%. Analysis of sequence revealed the presence of two PVS strains in Colombia: three isolates were associated to PVSO (Ordinary) and twelve belonged to PVSA (Andean). A high diversity was observed among PVSA strains with percent identities in the range of 88-99%. These findings highlight the importance of strengthening seed certification programs and quarantine measures in Colombia for viruses like PVS, which can cause losses of up to 20% in potato crops and even higher in mixed virus infection.